2021
DOI: 10.5217/ir.2020.00021
|View full text |Cite
|
Sign up to set email alerts
|

Yarrow oil ameliorates ulcerative colitis in mice model via regulating the NF-κB and PPAR-γ pathways

Abstract: Background/Aims: Ulcerative colitis (UC) is a chronic inflammatory disorder with indefinite etiology; however, environmental, genetic, immune factors and microbial agents could be implicated in its pathogenesis. UC treatment is lifelong, therefore; the potential side effects and cost of the therapy are significant. Yarrow is a promising medicinal plant with the ability to treat many disorders, owing to its bioactive compounds especially the essential oil. The main aim of this research was to investigate the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Many studies have reported that PPAR- γ played a key role in mediating the anti-inflammatory effects ( Mohamed et al 2021 ; Choi et al, 2017 ; Chung et al 2003 ). Specifically, the PPAR signaling pathway was the most significantly higher and activated in the SR and SS groups than SC group, the results suggested that PPAR signaling pathway was sustained to relatively high level, when resistant to C. perfringens infection.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that PPAR- γ played a key role in mediating the anti-inflammatory effects ( Mohamed et al 2021 ; Choi et al, 2017 ; Chung et al 2003 ). Specifically, the PPAR signaling pathway was the most significantly higher and activated in the SR and SS groups than SC group, the results suggested that PPAR signaling pathway was sustained to relatively high level, when resistant to C. perfringens infection.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the nine extracts that we determined could enhance the activity of PPARα when used in conjunction with #419 have been discussed in previous studies, as shown below (Table 3). #203, an extract of Achillea millefolium , has an anti‐inflammatory effect through increasing PPARγ expression and inhibiting NFκB expression [61]. #213, an extract of Uncaria gambir , may increase the expression of PPARγ [62].…”
Section: Discussionmentioning
confidence: 99%
“…WB analysis was conducted with reference to previous reports [ 17 , 18 ]. Briefly, the proteins in the colon tissue lysates were separated by 10% SDS-polyacrylamide gel and blotted on the polyvinylidene difluoride membranes.…”
Section: Methodsmentioning
confidence: 99%